(untitled) (Journal of Population and Development, 2023)
This paper describes the labor migration of Shivasatakshi Municipality of Jhapa District. The main objective of this research study is to examine the foreign labor migration from Nepal to Gulf countries including Malaysia. Information was collected through 136 respondents and respondents’ households’ information and sample selection has been based on a systematic sampling method. The highest percentage of foreign labor migrants (23.53%) was found in the age group of 25-29 years. 55.88 percent of the respondents are married. About 44.12 percent of foreign labor migrants went to Malaysia due to unemployment. About 58.09 percent of respondents went for factory labor work. Hill Brahmin/Chhetri occupies the highest percentage. The Hill Brahmin/Chhetri respondents are 32.36 percent in first position and Tarai Janajati respondents are 26.47 percent in the research area. Most of the Hill Brahmin/Chhetri and Tarai Janajati people are involved in the agriculture sector and lack employment opportunities and services in other sectors. Moreover, this community is migrated from hills and holds less percentage of agricultural land in the research area. Due to unemployment and insufficient agricultural land, most Hill Brahmin/Chhetri and Tarai Janajati migrate to Gulf countries. Selection for Gulf countries as destinations by Hill Brahmin/Chhetri and Tarai Janajati people in the research area due to the low-privilege households and lack of skills in this manpower. The Government of Nepal should guarantee/ manage safer and better foreign labor migration. Foreign labor migration sends a large amount of remittance to Nepal, but they do not utilize it properly.